No Higher Honour : A Memoir of My Years in Washington - Rice, Condoleezza 1954- (London Simon & Schuster, 2011)
For eight years, Condoleezza Rice participated in the highest political councils and had a crucial role in shaping policy that affected not just America but the world. Here, she writes candidly of the many fascinating people with whom she interacted and the momentous events that tested her resolve.
Include Index
Keywords: Women cabinet officers -- United States -- Politics and government